Hepatoprotective Effect of Clerodendrum inerme Linn. Ethanolic Extract (The East and Central African Journal of Pharmaceutical Sciences, 2018)
Twenty four rats were divided into four equal groups. The control group received distilled water intraperitoneally. The second group received carbon tetrachloride 0.5 ml/kg for seven days while the third group was injected with carbon tetrachloride 0.5 ml/kg and simultaneously administered with Clerodendrum inerme extract 200 mg/kg orally for seven days. The fourth group received carbon tetrachloride 0.5 ml/kg intraperitoneally together with silymarin 200 mg/kg orally for seven days. At the end of treatment blood samples collected by direct cardiac puncture and serum were used for the marker enzymes aspartate aminotransferase, alanine aminotransferase, alkaline phosphatase, as well as cholesterol and triglyceride content. Rats treated with the ethanolic extract of C. inerme showed a significant decrease in the levels of the markers. The results obtained indicate that C. inerme Linn. protects the liver against carbon tetrachloride induced hepatotoxicity.
Keywords: Hepatoprotective; Glutathione; Clerodendrum inerme; carbon tetrachloride; aspartate amino transferase; alanine amino transferase; alkaline phosphatase